Hydrogen Sorption Kinetics of SiC-Coated Zr-1Nb Alloy; Coatings; Vol. 9, iss. 1 - Kashkarov E. B. Egor Borisovich; Syrtanov M. S. Maksim Sergeevich; Murashkina T. L. Tatiana Leonidovna; Kurochkin A. V. Aleksandr Viktorovich; Shanenkova Yu. L. Yuliya Leonidovna; Obrosov A. Aleksey (2019, 2019)
Title screen